Strategi Self Regulated Learning Siswa Kelas 12 SMA Selama Belajar Daring saat Pandemi COVID-19 - Rahma Diana, Intan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to examine self-regulated learning among 12th-grade high school students during online learning in the COVID-19 pandemic. This study used Zimmerman's theory. The method used is qualitative descriptive. The participants of the study were 3 12th-grade high school students, selected using purposive sampling techniques. Data were collected through online and face-to-face interviews. The data analysis technique used was thematic analysis. The results of this study show that all three students have self-regulated learning strategies, including Self-evaluation, Organizing and transforming, Goal setting, Keeping records and monitoring, Environmental structuring, Rehearsing, Seeking social assistance from peers, teachers and adults. The self-regulated learning strategies were implemented with the goal of achieving good grades to enter collage. The factors that influencing the students in implementing self-regulated learning strategies are motivation, goals, the surrounding environment, and the teaching methods provided by the teacher.